The role of 18F-fluciclovine PET in the management of prostate cancer: a systematic review and meta-analysis. Issue 11 (November 2019) - Kim, S.-J.; Lee, S.W.
Abstract : AIM: To investigate the diagnostic performance of 18 F-fluciclovine positron-emission tomography (PET) or combined PET and computed tomography (PET/CT) for diagnosis of primary cancer, preoperative lymph node (LN) staging, and detection of recurrent disease of prostate cancer (PCa) through a systematic review and meta-analysis. MATERIALS AND METHODS: The PubMed and EMBASE databases were searched from the earliest available date of indexing through 31 December 2018, for studies evaluating the diagnostic performance of 18 F-fluciclovine PET or PET/CT for the management of PCa patients. The sensitivities, specificities, and positive and negative likelihood ratios (LR+ and LR-) across the studies were calculated and summary receiver operating characteristic curves were constructed. RESULTS: Across 13 studies (563 patients), the pooled sensitivity for 18 F-fluciclovine PET or PET/CT for diagnosis of primary PCa was 0.87 (95% confidence interval [CI]: 0.77–0.93) and a pooled specificity of 0.84 (95% CI: 0.68–0.93). For LN staging, the pooled sensitivity was 0.56 (95% CI: 0.37–0.74) and a pooled specificity of 0.98 (95% CI: 0.88–1.00). For detection of recurrent disease, the pooled sensitivity was 0.79 (95% CI: 0.60–0.91) and a pooled specificity of 0.69 (95% CI: 0.59–0.77). In meta-regression analysis, no definite variable was the source of the study heterogeneity. CONCLUSION: The current meta-analysis showed the moderate sensitivity and specificity of 18 F-fluciclovine PET or PET/CT for the diagnosis of primary cancer, preoperative LN staging, and detection of recurrent PCa. Further large multicentre studies will be necessary to substantiate the diagnostic accuracy of 18 F-fluciclovine PET/CT for management of PCa patients. Highlights: The pooled sensitivity was 0.87 and a pooled specificity was 0.84 for primary PCa. The pooled sensitivity for recurrent PCa was 0.79 and a pooled specificity of 0.69. F-18 fluciclovine PET or PET/CT showed moderate sensitivity and specificity of for management of PCa.